Influence of chemically p-type doped active organic semiconductor on the film thickness versus performance trend in cyanine/C60 bilayer solar cells. Issue 3 (14th May 2015) - Jenatsch, Sandra; Geiger, Thomas; Heier, Jakob; Kirsch, Christoph; Nüesch, Frank; Paracchino, Adriana; Rentsch, Daniel; Ruhstaller, Beat; C Véron, Anna; Hany, Roland
Abstract: Simple bilayer organic solar cells rely on very thin coated films that allow for effective light absorption and charge carrier transport away from the heterojunction at the same time. However, thin films are difficult to coat on rough substrates or over large areas, resulting in adverse shorting and low device fabrication yield. Chemical p-type doping of organic semiconductors can reduce Ohmic losses in thicker transport layers through increased conductivity. By using a Co(III) complex as chemical dopant, we studied doped cyanine dye/C60 bilayer solar cell performance for increasing dye film thickness. For films thicker than 50 nm, doping increased the power conversion efficiency by more than 30%. At the same time, the yield of working cells increased to 80%. We addressed the fate of the doped cyanine dye, and found no influence of doping on solar cell long term stability.